PREVALENCE OF CONGENITAL COLOR BLINDNESS AMONG UNDER GRADUATE MEDICAL STUDENTS - L.SUBHA,; M.RAMYAA,; M.S.RAJARATHINAM, (International Journal of Pharma and Bio Sciences, 2015)
Congenital colour blindness is a common X-Linked genetic disorder, with a prevalence of approximately 5% in Asian males in the general population. Though it creates less problems in day to day life, certain professions demand a high degree of colour perception. This study estimates the prevalence of congenital colour blindness among undergraduate medical students. Colour vision of 568 undergraduate medical students was tested using Ishihara’s colour plates. Eleven male students were found to have defective colour vision, out of which only one was aware of his defect. This study was conducted to help the undergraduate students to persue a speciality subject which does not require a high degree of colour perception.